Observation of unexpected molecular binding activity for Mu phage tail fibre chaperones. (30th August 2019) - Sakai, Kohei; Iwazaki, Takuma; Yamashita, Eiki; Nakagawa, Atsushi; Sakuraba, Fumiya; Enomoto, Atsushi; Inagaki, Minoru; Takeda, Shigeki
Abstract: In the history of viral research, one of the important biological features of bacteriophage Mu is the ability to expand its host range. For extending the host range, the Mu phage encodes two alternate tail fibre genes. Classical amber mutation experiments and genome sequence analysis of Mu phage suggested that gene products (gp) of geneS (gpS = gp49) and gene S' (gpS' = gp52) are tail fibres and that gene products of geneU (gpU = gp50) and geneU' (gpU' = gp51) work for tail fibre assembly or tail fibre chaperones. Depending on the gene orientation, a pair of genes 49-50 or 52-51 is expressed for producing different tail fibres that enable Mu phage to recognize different host cell surface. Since several fibrous proteins including some phage tail fibres employ their specific chaperone to facilitate folding and prevent aggregation, we expected that gp50 or gp51 would be a specific chaperone for gp49 and gp52, respectively. However, heterologous overexpression results for gp49 or gp52 (tail fibre subunit) together with gp51 and gp50, respectively, were also effective in producing soluble Mu tail fibres. Moreover, we successfully purified non-native gp49-gp51 and gp52-gp50 complexes. These facts showed that gp50 and gp51 were fungible and functional for both gp49 and gp52 each other.